Clinicopathological analysis of idiopathic membranous nephropathy in different age groups - CAI Juan-juan; GU Kai-hong; GUO Yu; XU Dan; DUAN Ya-li; WENG Cang-ya; LU Chen (Linchuang shenzangbing zazhi)
Objective To explore the clinicopathological features of idiopathic membranous nephropathy(IMN) at different ages.Methods The clinicopathological data of 89 patients with IMN diagnosed by renal biopsy from May 2015 to May 2010 in the Xinjiang Uygur Autonomous Region People’s Hospital were retrospectively analyzed.The patients aged 18-76 years old(mean 45.2 ± 13.1),and the course of disease was 7 days-84 months(mean 12.4 ± 18.2 months).All patients were divided into four groups according to their age:less than 20 years old group(n = 4),20-39 years old group(n= 22),40-59 years old group(n = 40),over 60 years old group(n= 11).The clinical indexes,pathological typing and immunofluorescence examinations were analyzed.Results The highest peak of IMN was 40 to 59 years old(52 cases,58.4%).The clinical manifestations of the nephrotic syndrome were the most(66 cases,74.2%),followed by edema(63 cases,70.8%).The clinical data of IMN patients at different ages showed significant difference(P<0.05) in systolic blood pressure,diastolic blood pressure,total cholesterol,serum creatinine,uric acid,and 24-h urine protein.The incidence of hypertension and hyperlipidemia was significantly higher in 40-59 years old group and over 60 years old group than in less than 20 years old group.The renal pathological changes of renal tubular-interstitial damage and arterial wall thickening in 40-59 years old group and over 60 years old group were more serious than in less than 20 years old group and 20-39 years old group.The pathological staging was the most common in stage Ⅲ(34 cases,38.2%),and the stage Ⅱ(20 cases,22.5%).Immunofluorescence staining revealed that IgG deposition was most seen(86 cases,96.6%),followed by C3 deposition(55 cases,61.8%).Conclusions IMN is commonly seen in mid-aged males of over 40 years old.The main manifestation is nephrotic syndrome.In IMN patients over 40 years old,systolic blood pressure,diastolic blood pressure,total cholesterol,serum creatinine,and uric acid are higher,and the renal interstitial damage and arterial wall thickening are more serious.Early renal biopsy is necessary for IMN patients in order to clarify the pathological type and the progress of the disease.It has very important significance to carry out the treatment plan and delay the disease progression.